Role of Yogasana in the Management of Hypothyroidism - Kodag, Shubhangi; Swasthvrita (International Research Journal of Ayurveda & Yoga, 2024)
Hypothyroidism main occur as a result of primary gland failure or insufficient thyroid gland stimulation by the hypothalamus or pituitary gland. Hypothyroidism is a common endocrine disorder resulting from deficiency of thyroid hormone. Hypothyroidism is a relatively common condition with an approximate prevalence of 2% in adult women. The best Laboratory assessment of thyroid function which serum TSH test. Thus a multifactorial and Holistic approach is required in successfully managing the condition of hypothyroidism i.e. diet, yogic exercises all in combination helps in normalizing the thyroid function in hypothyroidism.